Phase 3 Study of Talazoparib Plus Enzalutamide Versus Placebo Plus Enzalutamide as First‐Line Treatment in Patients With Metastatic Castration‐Resistant Prostate Cancer: TALAPRO‐2 Japanese Subgroup Analysis - Nobuaki Matsubara; Hideaki Miyake; Hiroji Uemura; Atsushi Mizokami; Hiroaki Kikukawa; Takeo Kosaka; Kazuo Nishimura; Motonobu Nakamura; Kazuki Kobayashi; Atsushi Komaru; Yuko Mori; Shigeyuki Toyoizumi; et al. (Cancer Medicine)
ABSTRACT Background In TALAPRO‐2, the poly(ADP‐ribose) polymerase inhibitor talazoparib plus the androgen receptor–signaling inhibitor enzalutamide improved radiographic progression‐free survival (rPFS) versus placebo plus enzalutamide (hazard ratio [HR] = 0.63; 95% CI, 0.51–0.78) in molecularly unselected patients with metastatic castration‐resistant prostate cancer (mCRPC). We report an exploratory analysis of efficacy, safety, and pharmacokinetics in Japanese patients enrolled in the TALAPRO‐2 study. Methods The ongoing, multinational, randomized, double‐blind, phase 3 TALAPRO‐2 study enrolled patients with mCRPC receiving ongoing androgen deprivation therapy. Patients were prospectively assessed for homologous recombination repair (HRR) gene alterations and randomized 1:1 to receive talazoparib or placebo plus enzalutamide once daily. The primary endpoint was rPFS by blinded independent central review (BICR). Secondary endpoints included overall survival, objective response, safety, and pharmacokinetics. Results For the 116 Japanese all‐comers patients enrolled in TALAPRO‐2, the HR for rPFS was 0.89 (95% CI, 0.45–1.75) for the talazoparib versus placebo arm; among those with HRR‐deficient disease, the HR was 0.58 (95% CI, 0.16–2.20). Among patients with BRCA1/2 gene alterations in the HRR‐deficient population (n = 10), the HR for rPFS was < 0.01 (95% CI, < 0.01–not reached) for the talazoparib versus placebo arm. In the all‐comers population, the objective response rate by BICR was 55% (all complete responses) in the talazoparib arm versus 36% in the placebo arm. The safety profile of talazoparib plus enzalutamide was similar between Japanese patients and the overall all‐comers population; no new safety signals were identified. Anemia was the most common grade 3/4 treatment‐emergent adverse event (55%) and cause of talazoparib discontinuation (12%). Talazoparib Ctrough was comparable across Japanese, Asian, and non‐Asian subgroups. Conclusions In this exploratory analysis, efficacy outcomes with talazoparib plus enzalutamide in Japanese patients in TALAPRO‐2 were consistent with those in the overall all‐comers population. The safety profile and pharmacokinetics of the combination were similar between Japanese patients and the overall all‐comers population. Trial Registration: ClinicalTrials.gov Identifier: NCT03395197